Asuhan Kebidanan Komprehensif Ny. S di Tempat Praktik Mandiri Bidan (PMB) - Siti Chodijah; Fransisca, Lidya; Rombe, Maritje; Hasanah, Hafizotun (STIKES Al-Su’aibah, 2024)
Comprehensive midwifery care is midwifery care that is provided comprehensively, in detail and continuously, starting from pregnant women, giving birth, postpartum and newborns, which is expected to reduce the maternal mortality rate which is the biggest problem in the world today. (Minister of Health of the Republic of Indonesia, 2020) The research design used was descriptive observation and case study research. Midwifery care uses midwifery management based on Varney's 7 steps in Mrs. S aged 33 years G3P2A0 32 weeks pregnant at TPMB Midwife. The period of childbirth and up to using a long-term contraceptive method, namely the IUD in postpartum, is 42 days. Comprehensive midwifery care has been provided to Mrs. S from pregnancy, childbirth, newborns and postpartum examination results were found to be within normal limits. Comprehensive midwifery care has been provided to Mrs. S from pregnancy, childbirth, newborns and postpartum examination results were found to be within normal limits.